Plano de emergência em aterros sanitários: aspectos relevantes a partir de um estudo de caso no Rio Grande do Sul - Borges, Fernando Lima (Universidade do Vale do Rio dos Sinos, 2011)
The sanitary landfills have specific norms, where the minimum criteria for project, implantation and operation are established. In intention to collaborate with the prevention of ambient impacts and provoked risks the health in situations of emergencies in this type of enterprise, this article was elaborated with the objective to present through study of a case of the Rio Grande do Sul, excellent information to be considered in the elaboration of the plan of emergencies for places with disposal of urban solid residues in the form of fills with earth bathroom. The theorical base was norm ABNT NBR 13896:1997 that establishes criteries for project, implantation and operation of landfills of not-dangerous wastes. The analysis of the normative requirements and the study of case had allowed to conclude that many excellent aspects are not considered in the project phase and the main emergencies are related the operational problems associates to the lack of preventive inspections, operational control and inadequate sizings in the project phase.
Keywords: Resíduo sólido urbano; Aterro sanitário; Plano de emergência; Urban solid waste; Sanitary landfill; Emergency plan